2018
DOI: 10.1002/ecy.2414
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up linkages between primary production, zooplankton, and fish in a shallow, hypereutrophic lake

Abstract: Nutrient supply is a key bottom-up control of phytoplankton primary production in lake ecosystems. Top-down control via grazing pressure by zooplankton also constrains primary production and primary production may simultaneously affect zooplankton. Few studies have addressed these bidirectional interactions. We used convergent cross-mapping (CCM), a numerical test of causal associations, to quantify the presence and direction of the causal relationships among environmental variables (light availability, surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 70 publications
6
51
1
Order By: Relevance
“…Furthermore, fish biomass in lakes is primarily driven by bottom-up effects (e.g. Hanson & Leggett, 1982; Lemmens et al , 2018; Matsuzaki et al , 2018) – a finding also revealed in our study at the aggregate biomass level, which did not differ among lake types despite radically different fish community composition. As species richness was substantially lower in unmanaged lakes, the lake type-specific small-bodied non-game species that colonized unmanaged lakes can reach higher biomasses and abundances in these lakes types compared to managed lakes.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, fish biomass in lakes is primarily driven by bottom-up effects (e.g. Hanson & Leggett, 1982; Lemmens et al , 2018; Matsuzaki et al , 2018) – a finding also revealed in our study at the aggregate biomass level, which did not differ among lake types despite radically different fish community composition. As species richness was substantially lower in unmanaged lakes, the lake type-specific small-bodied non-game species that colonized unmanaged lakes can reach higher biomasses and abundances in these lakes types compared to managed lakes.…”
Section: Discussionsupporting
confidence: 83%
“…Ibaraki Prefecture, which includes the Lake Kasumigaura watershed, is the top producer of some vegetables in Japan. Although these agricultural activities have supported farming livelihoods and the local economy, they have resulted in the eutrophication of Lake Kasumigaura, which is currently hypereutrophic (Takamura 2012, Matsuzaki et al 2018).…”
Section: Study Areamentioning
confidence: 99%
“…This watershed is highly nitrogen-loaded by agriculture (Matsumori and Itahashi 2009, Shindo et al 2009), and Matsuzaki et al (2018 have recently reported that the primary production of Lake Kasumigaura is controlled by nitrogen. This watershed is highly nitrogen-loaded by agriculture (Matsumori and Itahashi 2009, Shindo et al 2009), and Matsuzaki et al (2018 have recently reported that the primary production of Lake Kasumigaura is controlled by nitrogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, at high CED om , the realized phytoplankton biomass (measured through the residuals of the Chl a to TP relationship: TP‐corrected Chl a ) was expected to be higher than at low CED om . In turn, we expected that phytoplankton biomass (Chl a ) would also be a good predictor of fish community production (CP om ) so that a bottom‐up trophic cascade would cause increased production of the fish community in phytoplankton‐rich lakes, as described in terms of community composition and biomass (Brucet et al ; Arranz et al ; Matsuzaki et al ).…”
mentioning
confidence: 99%